Faktor Risiko Kanker Kolorektal - Naufal Rasyid Aswan; Rizki Hanriko (CV. Jasa Sukses Abadi, 2023)
Colorectal cancer is cancer of the colon or rectum. Colorectal cancer is the third most common cancer in men and second in women, and according to data from the World Health Organization (WHO), colorectal cancer accounts for nearly 1.4 million new cases every year worldwide. In 2017, there were 1.8 million cases of colorectal cancer worldwide, with a standard incidence rate of 23.2 cases per 100,000 person-years. This article is a literature compiled to analyze the risk factors associated with colorectal events. The references used are articles published between 2012-2022. Colorectal cancer risk factors are divided into modifiable risk factors and non-modifiable risk factors. The most dominant non-modifiable risk factor is a history of IBD, followed by a family history of cancer, history of diabetes, age and gender. The most dominant modifiable risk factor is psychosocial stress, followed by alcohol consumption, smoking history, and obesity.